Observational study on Takotsubo-like cardiomyopathy: clinical features, diagnosis, prognosis and follow-up. Issue 5 (11th October 2012) - Cacciotti, Luca; Passaseo, Ilaria; Marazzi, Giuseppe; Camastra, Giovanni; Campolongo, Giuseppe; Beni, Sergio; Lupparelli, Fabrizio; Ansalone, Gerardo
Abstract : Objectives: The present study attempts to identify appropriate elements that may contribute to clarify the broad clinical features (diagnosis, care, complication and prognosis) of Takotsubo-like cardiomyopathy for improving its management. Design study: Observational study. Setting: Primary level of care referred to the emergency department of Vannini Hospital, Rome, Italy. Participants: The study population consisted of 75 patients, 72 of the them were women and 3 were men with a mean age of 71.9±9.6 years. Methods: From February 2004 to November 2010, prospectively included 84 consecutive patients diagnosed for suspected Takotsubo-like cardiomyopathy. To be eligible, patients had to meet all the Mayo clinic criteria in the absence of neurological trauma or intracranial haemorrhage. Moreover, those patients that at follow-up still presented alteration of acute phase at ECG and echocardiogram were excluded. Thus, 75 patients comprised the study population. To follow-up 19 patients were lost. Results: None of 75 patients died in acute phase. All patients were promptly discharged (8.4±4.4 days), since they recovered their normal functional status without symptoms. Follow-up information was available for 56 patients. At a mean follow-up time of 2.2±2 years (range, 0.1–6.8 years) two octogenarian patients (2.6%) died because of sudden cardiac death and pulmonary embolism, respectively. The Takotsubo-like cardiomyopathy recurred in one patient. Conclusions: The results of this study support the previous reports about the good prognosis, also in critically ill patients, of Takotsubo-like cardiomyopathy. Further assessment will be needed to determine a careful and sustained follow-up for choosing the best care and foreseeing the recurrences of this emerging condition.